Penerapan Ritel Modern Aplikasi Alfagift dan dampaknya pada Kepuasan Konsumen - Aulia Fauziah (Asosiasi Ahli Administrasi Indonesia, 2024)
This study aims to analyze impact of modern retail implementation through the Alfagift application on consumer satisfaction in the Bandung Raya region. Using a quantitative descriptive approach, the study involved 103 respondents who had made purchases through Alfagift. The results of simple regression analysis indicate that 74.6% of consumer satisfaction is influenced by the implementation of modern retail through Alfagift. Hypothesis testing confirms a significant influence between modern retail, the Alfagift application, and consumer satisfaction. This study offers a comprehensive insight into the correlation between modern retail and consumer satisfaction, with Alfagift as a case study. Although 25.4% of other influences remain unexplained, these findings lay the groundwork for further exploration of additional factors affecting consumer satisfaction in the context of modern retail through Alfagift.